2010
DOI: 10.1002/kpm.338
|View full text |Cite
|
Sign up to set email alerts
|

Extending the task–artifact framework with organizational learning

Abstract: Over the past decade there has been an increased focus on the importance of contextual factors in all IT disciplines. At the same time, scholars have heeded the call for investigating the creation of more effective synergies between science and design. For example, the task-artifact (TA) framework was developed to support better utilization of behavioral, cognitive, and social science in Human-Computer Interaction (HCI) design. This framework is based on the general developmental pattern of human activities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In summary, core articleswhere the notion of artifacts was used to develop the core ideas in a significant wayproposed measurements of artifacts or knowledge objects (Bolsani and Oltramari, 2012;Zuo and Panda, 2013); discussed frameworks for analysis where artifacts played crucial roles (e.g. Borgo and Pozza, 2012;Di Mario, 2013;Shariq, 1998); highlighted the human-computer interactions in knowledge management systems or processes (Jiang et al, 2010;Martin et al, 2012;Rountree et al, 2002;Sánchez-Alonso and Frosch-Wilke, 2005;Maaninen-Olsson et al, 2008); focused on the relationship between artifacts/objects and knowledge dynamics at the group (Holford, 2014;Singh et al, 2009) or network levels (Hustad, 2007;Kreiner, 2001); or discussed the role of cognitive, organizational and managerial variables (Padova and Scarso, 2012) that influenced the management of artifacts/objects to enhance stability and reduce conflict (Svabo, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, core articleswhere the notion of artifacts was used to develop the core ideas in a significant wayproposed measurements of artifacts or knowledge objects (Bolsani and Oltramari, 2012;Zuo and Panda, 2013); discussed frameworks for analysis where artifacts played crucial roles (e.g. Borgo and Pozza, 2012;Di Mario, 2013;Shariq, 1998); highlighted the human-computer interactions in knowledge management systems or processes (Jiang et al, 2010;Martin et al, 2012;Rountree et al, 2002;Sánchez-Alonso and Frosch-Wilke, 2005;Maaninen-Olsson et al, 2008); focused on the relationship between artifacts/objects and knowledge dynamics at the group (Holford, 2014;Singh et al, 2009) or network levels (Hustad, 2007;Kreiner, 2001); or discussed the role of cognitive, organizational and managerial variables (Padova and Scarso, 2012) that influenced the management of artifacts/objects to enhance stability and reduce conflict (Svabo, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…20 Issue: 6, pp.1333-1352, https://doi.org/10.1108/JKM-05-2016 Young (Padova and Scarso, 2012); digitalized artifacts such as still photographs or nonimmersive photorealistic virtual reality to teach visual image analysis (Rountree et al, 2002); ZingThing™ groupware and cognitive artifacts such as group discussions employed in an educational context (Sing et al, 2009); and principles and methods for evaluation in a virtual organization (Zuo and Panda, 2013). (Jiang et al, 2010;Martin et al, 2012;Rountree et al, 2002;Sánchez-Alonso and Frosch-Wilke, 2005), or knowledge integration processes (Maaninen-Olsson et al, 2008). Finally, a discrete number of articles focused on the relationship between artifacts/objects and knowledge dynamics, studying how objects interacted with subjects in groups (Holford, 2014;Singh et al, 2009), contributed to networks evolution (Hustad, 2007), stability or conflict (Svabo, 2009), boundary breaking outcomes due to lack of assessment tools (Kreiner, 2001), or how other intervening variables such as cognitive, organizational and managerial actions (Padova and Scarso, 2012) influenced the management of artifacts or objects (see also Mariano, 2010).…”
Section: Core Articles Shaping the Current Debatementioning
confidence: 99%
“…At the macro level, it was found that structural, behavioral and cognitive factors were likely to influence the co-creation of artifacts in collaborative knowledge building. Structural factors included organizational rules (Shariq, 1998; Schwabe and Salim, 2002; Kim et al , 2002) and workplace setting (Aarrestad et al , 2015; Padova and Scarso, 2012; Jiang et al , 2010; Lamproulis, 2007). Organizational rules were discussed with regards to the organizational system as a whole where the tools (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Along with organizational rules, workplace setting was also addressed as a potential structural factor influencing the co-creation of artifacts in collaborative knowledge building. In particular, physical space (Lamproulis, 2007), collaborative space (Aarrestad et al , 2015), organizational arrangements (Padova and Scarso, 2012) and a good fit between artifacts type and organizational context (Jiang et al , 2010) all seemed to directly influence the co-creation process and the corresponding artifact production because a proper collaborative space was found to enlarge “the sensory-motor connectivity in knowledge creation” (Aarrestad et al , 2015, p. 88) and contribute to shared meanings of actions and behaviors (Lamproulis, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation